2015
DOI: 10.1007/s00228-014-1795-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABCB1 polymorphisms with prognostic outcomes of anthracycline and cytarabine in Chinese patients with acute myeloid leukemia

Abstract: The findings suggested the TTT haplotype was possibly related to the OS, RFS, and relapse in Chinese patients with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…[34][35][36] Both the ABCB1*2 and 1236C>T have significant effect on oxaliplatin 37) susceptibility and sunitinib toxicities and survival. 38) Megías-Vericat et al reported the influence of each SNP on the effectiveness of cytarabine plus anthracyclines 39) while He et al emphasized on the impact of the haplotype on the effectiveness of the same therapy. 40) The impact of the ABCB1 1236C>T SNP rather than the ABCB1*2 haplotype in this study is consistent with a previously published clinical study of methadone 41) and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Both the ABCB1*2 and 1236C>T have significant effect on oxaliplatin 37) susceptibility and sunitinib toxicities and survival. 38) Megías-Vericat et al reported the influence of each SNP on the effectiveness of cytarabine plus anthracyclines 39) while He et al emphasized on the impact of the haplotype on the effectiveness of the same therapy. 40) The impact of the ABCB1 1236C>T SNP rather than the ABCB1*2 haplotype in this study is consistent with a previously published clinical study of methadone 41) and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…In 263 intermediate-risk Chinese AML patients treated with anthracycline and cytarabine, He et al54 investigated the influence of polymorphisms G2677T/A, C1236T, and C3435T. This study reported that patients with TTT haplotype had a longer OS compared with those without TTT haplotype, and hence TTT haplotype was possibly related to the OS, EFS, and relapse in Chinese patients with AML.…”
Section: Abcb1 Variants and Aml Treatmentmentioning
confidence: 99%
“…4 Recent studies have found that MDR1 polymorphism is not only an important genetic factor affecting the response of cancer patients to chemotherapy drugs but is also related to patients’ susceptibility to disease and clinical manifestations. 5–7…”
Section: Introductionmentioning
confidence: 99%